Composition Of Rattan Communities (Arecaceae, Subfamily Calamoideae) In Forest Reserves Of Penang - Wan Nur Fasihah Zarifah, W Rozali (2014)
There is a limited data collection on distribution patterns, species abundance, and species composition of rattan elsewhere in the country. An efficient survey will provide biological material to improve knowledge of botany and ecology. Terdapat koleksi data yang terhad terhadap corak taburan, kelimpahan species dan komposisi spesies rotan di kawasan yang berlainan di negara ini. Satu tinjauan yang efisien akan menyumbangkan bahan biologi untuk meningkatkan pengetahuan botani dan ekologi.